Papel do MHC de classe II na biogênese do vacúolo parasitóforo de Leishmania amazonensis e seu impacto no curso da infecção in vivo - Silva, Fabiana (2014)
L. amazonensis are obligate intracellular protozoan, engulfed by host immune cells and multiply in membrane-bound compartments called parasitophorous vacuole (PV). These undergo a maturation process that includes the endocytic vesicles fusions conferring via a hybrid nature, inducing the formation of large vacuoles which may contain up to 30 amastigotes. The VP biogenesis involves acquisition of late endosomes membrane markers as lamps, Rab GTPases, cathepsin, proton ATPases, and MHC class II. In these VPs MHC II molecules are located in the same binding site of L. amazonensis amastigotes, which are able to degrade this molecule in megassomos. In this context, we aimed to verify whether the MHC II molecule is important in the VP biogenesis and his absence would affect the course of infection. For this we performed in vivo assays in which we infect Paws of MHC II (mhcii-/-) knockouts and wild type (WT) C57BL / 6, and after 6 weeks of infection, we collected spleen, popliteal lymph node and paw for histopathological analysis, cytokine profile and parasitic load. In addition, we made a multiplication assay, in times of 72, 96 and 120 hours, with peritoneal macrophages of mice mhcii-/- and WT infecting them via intraperitoneal, with amastigotes of L. amazonensis. The results of the histological analysis showed that infected animals mhcii-/- showed no significant difference compared to WT mice. Regarding cytokine production, the results showed increased production of IL -4 and IL -12 in mhcii-/- animal and more significant increase in IFN-γ in WT animals, even with a reduction of TNF- α in two groups analyzed. In the proliferation assay with peritoneal macrophages, it was observed decreased in the parasitophorous vacuole area and lower parasite load in mhcii-/- animals compared to WT mice. Therefore , the process of colocalization of MHC II molecules on the membrane of the VP seems to be not only a mechanism of subversion of the parasite , whereas in the absence of this molecule was highly significant decrease in the VP area and lower parasite load , featuring less progression of disease compared to WT mice. Thus, we believe that the MHC II molecule may also play a role in the biogenesis of the VP.